Biochar and renewable energy generation from poultry litter waste: A technical and economic analysis based on computational simulations. (15th December 2015) - Huang, Y.; Anderson, M.; McIlveen-Wright, D.; Lyons, G.A.; McRoberts, W.C.; Wang, Y.D.; Roskilly, A.P.; Hewitt, N.J.
Abstract : Graphical abstract: Highlights: A techno-economic analysis of the production of biochar and heat and power from poultry litter. The bio-waste pyrolysis/gasification system is modelled and simulated. The poultry litter biochar production system integrated with a CHP installation offers a significant CO2 saving opportunity. Gate fees, Carbon Credits and ROCs have a significant impact on the breakeven selling price of biochar produced. Abstract: The technical and economic analysis of generating biochar together with electricity and/or heat from poultry litter (PL) waste is the subject of this study. To carry out this study, the process simulation software ECLIPSE is used. Modelling and simulation have been conducted over the selected system: the pyrolysis/gasification process integrated with an Organic Rankine Cycle (ORC). The facility will be capable of processing 1500 kg of PL every hour. The simulation shows that when a reference PL is used the yield of biochar from the process is around 398 kg/h with a 38% carbon content. Electricity generated by the ORC system is 388 kW he . Recovered low grade heat for space heating is estimated at 1831 kW hth . The results of the economic analysis suggest that when paying £20/tonne for handling and storing the feedstock without any options of selling either heat or electricity, the break-even selling price (BESP) of biochar is around £218/tonne. If the sale of electricity and heat produced is considered to be around £60/MW he and £5/MW hth, the BESP will decrease to £178/tonne. The case studies also indicate that when a gate fee of £10/tonne is introduced the BESP can be further reduced to £65/tonne, equivalent to a 63% reduction. On the other hand if biochar generated has an average price of £150/tonne in the market and the plant receives one Renewable Obligation Certificate (ROC) from the Government, the Levelised Cost of Electricity (LCOE) for the electricity generation will be £46/MW he, which is compatible with electricity generated by fossil fuel power plants.